FACE E POLIDEZ EM ENTREVISTA TELEVISIVA NO PERÍODO DE ELEIÇÕES PRESIDENCIAIS - RENATA GONÇALVES GONDIM (2023)
This research aims to analyze politeness and facework strategies employed by Jair Bolsonaro in a verbal interaction. We intend to highlight the linguistic mechanisms used by him to avoid questions that threaten his face. Therefore, the corpus is composed of a television interview given to Jornal Nacional, aired by Globo, a television broadcasting channel, during the 2022 presidential elections. The theoretical framework is based on the principles of Conversation Analysis, mainly on the studies of Goffman (1967), Brown and Levinson (1987), Marcuschi (2003), Kerbrat-Orecchioni (2006), Preti (2003), among others. The interview was broadcast on August 22nd 2022, and it opened a series of interviews by Willian Bonner and Renata Vasconcellos with the candidates for the Presidency of the Republic for the term from 2023 to 2026. The main topics of the interview were: the fight against corruption, the pandemic, the economy, fake news on social media, among others. According to the findings, we point out that the procedures used by Bolsonaro sought to soften possible negative situations, distancing him from issues that could threaten his positive image, in order to promote engagement and identification with the viewers, who are ultimately the voters. KEYWORDS: Face; Politeness; Interview; Presidential Elections.